IMPLEMENTATION OF THE TAGUCHI METHOD WITH TRAPEZOIDAL FUZZY NUMBER IN THE TOFUPRODUCTION PROCESS - Wungguli, Djihad; Isa, Jefri N.; Payu, Muhammad Rezky Friesta; Nurwan, Nurwan; Nasib, Salmun K; Junus, Stella (PATTIMURA UNIVERSITY, 2023)
Indonesians consume more tofu every week, proving that it is one of the country's most well-liked and potential food ingredients. Therefore, several people benefit from this positive potential as a business opportunity and improve the quality of their products as part of a market competition strategy. This study uses the Taguchi method and fuzzy logic to optimize the multi-response characteristic tofu production process. These multi-responses include water and protein content, each of which has the characteristics of